Mediating role of motivation in the relationships between awareness, accessibilty, perceived organizational support and adoption of ict among extension agents in North-East, Nigeria - Mustapha, Sa'adu (2021)
Agricultural extension is described as one of the fields where ICTs can have a significant impact that is largely dependent on knowledge sharing between extension agents and a wide range of other actors. Poor infrastructure makes visiting remote areas more difficult and expensive. The number of extension agents in the study area are inadequate to meet the farmers population. This study was designed to determine the mediating role of motivation in the relationships between awareness, accessibility, perceived organizational support and adoption of ICT among extension agents in northeast, Nigeria. Specifically, the study was conducted to: 1) determine the respondents‘ level of ICT adoption; 2) identify the respondents level of awareness, accessibility, perceived organizational support and motivation; 3) clarify the relationship between awareness, accessibility, perceived organizational support, motivation and adoption of ICTs among the respondents; 4) examine the most influential factors influencing the adoption of ICTs among the respondents; and 5) examine the mediation role of motivation in relationships between awareness, accessibility, perceived organizational support and adoption of ICT‘s among extension agents. The study used Piaget Constructivism Theory (1980), the Digital Divide Theory (Van Dijk, 2009) and Vroom‘s Expectancy Theory (1964). The study employed the quantitative approach and descriptive correlational research design. A sample of 254 extension agents was randomly selected. The data was obtained by using a self-administered questionnaire and analysed using descriptive statistics, Pearson product-moment correlation, multiple linear regression and structural equation modelling. The findings from the study indicated that the level of ICT adoption was high, awareness, accessibility, and motivation were moderate, perceived organizational support was low. High and positive relationship between awareness and ICT adoption (r=.938; p=.000), accessibilityand ICT adoption (r=.731; p=0.00), motivation and ICT adoption (r=.215; p=.001). The results of the multiple regression analysis revealed that four variables (marital status, awareness, accessibility and motivation) contributed significantly to ICT adoption in extension work. The multi-model analysis conducted in this study revealed that the mediated model is better than the direct model in explaining the inter-relationships. It had an R2 of 0.47 against 0.23 of the direct models. The final model achieved the required categories of the fit indices (Relative chi-square = 2.045; CFI = .949; IFI = .949; NFI = .906; RMSEA = .064). The study concluded that motivation exhibit a partial mediation in the relationships between awareness, accessibility, perceived organizational support and adoption of ICTs. Hence, it is recommended that extension organizations should be mindful of the motivation levels of their employee; such could facilitate the adoption of ICT in extension work.